2007
DOI: 10.1038/sj.onc.1210724
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic pathways impinging on the G2-restriction point

Abstract: In the absence of mitogenic stimuli, cells normally arrest in G 1/0 , because they fail to pass the G 1 -restriction point. However, abrogation of the G 1 -restriction point (by loss of the retinoblastoma gene family) reveals a second-restriction point that arrests cells in G 2 . Serum-starvationinduced G 2 arrest is effectuated through inhibitory interactions of p27 KIP1 and p21 CIP1 with cyclins A and B1 and can be reversed through mitogen re-addition. In this study, we have investigated the pathways that al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…The level of cyclin D1 which promotes progression through G1/S phases was elevated, while cyclin B1, promoting G2/M transition, was barely present [45,46]. According with previous studies [47,48] the cyclins pro le was consistent with G2-arrest. However, broblasts seem to be long-term arrested rather than irreversible senescence since after treatment removal cells resumed proliferation even in case of prolonged exposure to Onco-P20 (Fig.…”
Section: Results Effect Of Onco D-p20 Treatment On Cell Proliferation supporting
confidence: 55%
“…The level of cyclin D1 which promotes progression through G1/S phases was elevated, while cyclin B1, promoting G2/M transition, was barely present [45,46]. According with previous studies [47,48] the cyclins pro le was consistent with G2-arrest. However, broblasts seem to be long-term arrested rather than irreversible senescence since after treatment removal cells resumed proliferation even in case of prolonged exposure to Onco-P20 (Fig.…”
Section: Results Effect Of Onco D-p20 Treatment On Cell Proliferation supporting
confidence: 55%
“…MAPKs have an important role in the G 2 /M transition. Recently, it has been shown that changes in the expression of c-Myc, Fos and DUSPs were associated with G 2 cell cycle arrest and re-entry into mitosis [48]. However the role of MAPKs signalling pathways on the G 2 /M arrest is not yet well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Both activation and inhibition of the ERK pathway have been associated with the G 2 /M delay [44 -47], and preincubation of cells with ERKs specific inhibitors not always abolishes the G 2 /M arrest [49,50] implying that progression through the G 2 /M phase is a complex process and that other pathways may be implicated. It has been shown that the PI3K/Akt may also contribute to the G 2 /M transition [48,49]. Further studies are needed to determine whether the response of Caco-2 cells to EA and urolithins involves the modulation of additional pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of checkpoint effector pathways by caffeine has been shown to increase sensitization to DNA damaging agents leading to cell death in several cell lines [39;40]. A recent report indicates that both the overexpression of c-MYC and the activating mutation of RAS were able to override the G2-restriction point in serum-starved mouse embryonic fibroblasts; however c-MYC overexpression resulted in increased apoptosis, whereas RAS activation resulted in continued proliferation in the absence of serum [41]. Studies by Knauf et al, demonstrated that expression of HRAS V12 in rat thyroid PCCL3 cells accelerated cell cycle progression after ionizing radiation, corresponding to an increase in chromosomal instability [42;43].…”
Section: Discussionmentioning
confidence: 99%